'Every picture tells a story': Interviews and diaries with children with cerebral palsy about adapted cycling. Issue 12 (18th June 2013) - Pickering, Dawn; Horrocks, Lyn Marie; Visser, Karen Susan; Todd, Gabriela
<x xml:space="preserve">Abstract</x> Aims The study aims to explore the effect of participation in adapted cycling on quality of life for children with cerebral palsy (CP). Methods The study used a qualitative approach developing creative mosaic methods using interviews and diaries. This study had two groups of children with CP: those who participated in adapted cycling and a control group who had not yet started. Children with CP aged 2–17 years who were already cycling were invited to take part in two interviews at the beginning and end of a 6‐week period and keep a cycling diary during this time. The control group of children with CP aged 2–17 years were asked to keep a diary of physical activities over 6 weeks and to take part in one interview at the end. Welsh, English, Bengali and Arabic were the languages spoken, and some children used communication aids. Results Results presented here include the first 25 children's interviews and diaries. The emergent themes from the analysis are: learning a new skill, the impact on wider family and friends, social participation and future aspirations. The diaries added an emotional dimension, by illustrations drawn by the children. Conclusion The children who took part in adapted cycling enjoyed this experience and it improved their sense of well‐being. Some in the control group went on to participate in adapted cycling. Physiotherapists can carry out creative research to hear the voices of children and young people with CP and incorporate their views and ideas into the development of service model delivery and treatment programmes.